Pembangunan Sistem Manajemen Logistic Dan Purchasing Pada Perusahaan Jasa Konstruksi (Studi Kasus: AMF-Haq Engineering and Consultant) - Akbar Fajariadi; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
AMF-Haq Engineering and Consultant is a company engaged in construction services. All items needed by the company are managed by the logistics and purchasing divisions. If the goods requested by other divisions exist and meet the demand, the inventory is released. If the requested item is not available or insufficient, the purchasing department will purchase the item. Until now, all these processes have been done manually by the logistics and purchasing divisions. All activities are still recorded in the book and the information process is also verbalized. The process of fulfilling goods within the AMF-Haq company is very important for the smooth running of the project. If the project works smoothly it will affect client satisfaction. Therefore, a logistics and purchasing management system was created. This system will be used by the logistics and purchasing divisions to manage the goods requirements of the AMF-Haq company. This system provides features of demand for goods, receipt of goods, issuance of goods, and purchases of goods. This system was built using the ReactJS library. In addition, it also uses GraphQL as a API that makes it easier to query the database. This system has been tested using white-box and black-box methods. In addition, Usability testing and compatible testing was also carried out to find out that the system could run on all web browsers. Testing shows that 100% of the needs have been met and are valid.